2009
DOI: 10.1038/sc.2009.56
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of using auto-titrating continuous positive airway pressure to treat obstructive sleep apnoea after acute tetraplegia

Abstract: Study design: A prospective cohort with acute tetraplegia. Objectives: Obstructive sleep apnoea (OSA) is common within weeks of tetraplegia. This study aimed at determining the feasibility of auto-titrating continuous positive airway pressure (CPAP) to treat OSA after acute tetraplegia. Setting: The Victorian Spinal Cord Service, Melbourne, Australia Methods: Participants underwent full, portable polysomnography. Those with an apnoea hypopnoea index of more than 10 events per hour were defined as having OSA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…9 It is likely that the increased nasal resistance observed in this study contributes to both of these observations. In otherwise healthy individuals, nasal packing 13 can give rise to OSA and nasal decongestion with steroids and an α-adrenergic agent (dexamethasone and tramazoline) can reduce OSA severity in the able-bodied.…”
Section: A B Cmentioning
confidence: 69%
See 2 more Smart Citations
“…9 It is likely that the increased nasal resistance observed in this study contributes to both of these observations. In otherwise healthy individuals, nasal packing 13 can give rise to OSA and nasal decongestion with steroids and an α-adrenergic agent (dexamethasone and tramazoline) can reduce OSA severity in the able-bodied.…”
Section: A B Cmentioning
confidence: 69%
“…[2][3][4][5][6][7] Untreated OSA is a significant issue in tetraplegia as it is associated with significant neurocognitive deficits, sleepiness, and reduced quality of life. [2][3][4][5][6]8,9 Tetraplegia is likely to compromise the patency of the nose because sympathetic outflow to the upper airway is typically disrupted after cervical spinal cord injury. In an animal model, unopposed parasympathetic activation of the upper airway was observed to increase nasal airflow resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Using the same criteria, the same authors reported in a cross sectional study of 78 patients a prevalence of 91% in acute complete tetraplegia and a prevalence of 56% in patients with acute incomplete tetraplegia. There was no relationship between the neurological level and AHI.…”
Section: Prevalencementioning
confidence: 93%
“…Current data suggest CPAP adherence rates of 23-74% and those who are more sleepy are more likely to be adherent. 9,11 Reasons for non-adherence include nasal congestion, claustrophobia, inability to adjust the mask and anxiety. 9,11,12 There are no data investigating effective CPAP levels required to treat OSA in tetraplegia and whether this differs from able-bodied patients with OSA.…”
Section: Introductionmentioning
confidence: 99%